2005
DOI: 10.1002/ca.20100
|View full text |Cite
|
Sign up to set email alerts
|

Three-headed biceps brachii muscle associated with duplicated musculocutaneous nerve

Abstract: A unilateral three-headed biceps brachii muscle coinciding with an unusual variant of the musculocutaneous nerve was found during routine dissection of a 79-year-old male cadaver. The supernumerary bicipital head originated from the antero-medial surface of the humerus just beyond the insertion of the coracobrachialis, and inserted into the conjoined tendon of biceps brachii. Associated with this muscular variant was a duplicated musculocutaneous nerve. The proximal musculocutaneous nerve conformed to the norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 13 publications
(18 reference statements)
1
40
1
2
Order By: Relevance
“…The length of the additional head found in the present study (118.3 mm) is similar to that reported by Rincón et al [19], Ilayperuma et al [11] and some other authors [4,9] whereas Parasquevas et al [16] and Abu-Hijleh et al [1] reported a length of 65 mm and 95 mm, respectively. The width of this muscle head has been reported within a range of 15-24 mm [1,5,9,11,16,19,27], consistent with our findings. The characterisation of the size of the AHBB as thin, medium and thick, proposed in the present study, allows to enrich the descriptions of this structure.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The length of the additional head found in the present study (118.3 mm) is similar to that reported by Rincón et al [19], Ilayperuma et al [11] and some other authors [4,9] whereas Parasquevas et al [16] and Abu-Hijleh et al [1] reported a length of 65 mm and 95 mm, respectively. The width of this muscle head has been reported within a range of 15-24 mm [1,5,9,11,16,19,27], consistent with our findings. The characterisation of the size of the AHBB as thin, medium and thick, proposed in the present study, allows to enrich the descriptions of this structure.…”
Section: Discussionsupporting
confidence: 92%
“…Of note, a thick AHBB was found with the higher frequency (47.6%) in this work. Most prior reports [1,3,5,11,[19][20][21] coincide in indicating that the AHBB is innervated by the MCN. We have found 1 case of shared innervation between the MCN and the communicating branch of the median nerve.…”
Section: Discussionmentioning
confidence: 91%
“…In recently published literatures, only a few cases were presented where variation of the McN coexisted with a supernumerary-headed BBM: one showed the absence of the McN [2,3] and the other had a communicating branch to the MN [1,10]. According to Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…Neuromuscular anomalies are common in the upper limbs: the brachial plexus is the most variable part of the peripheral nervous system [6] and the biceps brachii muscle (BBM) is one of the most variable muscles in the human body [2]. Variations in the course and distribution of the musculocutaneous nerve (McN) [5] and the supernumerary head of the BBM [13] have been classified, because the prevalence of each variation reached about 34% and 22.4%, respectively [7].…”
Section: Introductionmentioning
confidence: 99%
“…3%. 5,6,7 Earlier workers studied racial differences in different races, among them the supernumerary third head of Biceps brachii is found in about 20.5%south African blacks, 8.3% of South African whites, 12% of black Africans, 9% Brazilian blacks, 20% of Brazilian white, 8% of Chinese, 37.5% of Colombians, 10% of white Europeans, 18% of Japanese, 2% Indian population and 15% of Turkish. 8,9 As far as the side preference for the third head of the Biceps brachii is concerned Sweiterand Carmichael emphasized that the incidence of such head is more on the right side, but in our observation it is on left side.…”
Section: Discussionmentioning
confidence: 99%